1990
DOI: 10.1111/j.1464-410x.1990.tb14753.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Response to Radiotherapy in Invasive Bladder Cancer

Abstract: The original pre-treatment histological sections from 125 patients with invasive (T2/T3) transitional cell bladder cancer treated by radical radiotherapy were studied; 63 tumours responded completely to radiation and 62 did not; 55 of 72 tumours containing areas of squamous metaplasia and 27 of 36 staining for beta-human chorionic gonadotrophin failed to respond to radiotherapy; 26 of 28 tumours showing both squamous metaplasia and beta-human chorionic gonadotrophin did not respond to radiation, whereas 40 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…At this time the lethal effects on the tumour should predominate over clonogenic repopulation from any surviving tumour cells. Other workers have shown that resistance to radiation treatment is seen in about half of all patients with T2/T3 bladder cancer treated with 55 Gy of fractionated radiotherapy, in agreement with our data (Jenkins et al, 1990). In the study cited above, the presence of squamous cell metaplasia and/or beta human chorionic gonadotrophin, but not the degree of aneuploidy, was associated with radiotherapy failure.…”
Section: Discussionsupporting
confidence: 83%
“…At this time the lethal effects on the tumour should predominate over clonogenic repopulation from any surviving tumour cells. Other workers have shown that resistance to radiation treatment is seen in about half of all patients with T2/T3 bladder cancer treated with 55 Gy of fractionated radiotherapy, in agreement with our data (Jenkins et al, 1990). In the study cited above, the presence of squamous cell metaplasia and/or beta human chorionic gonadotrophin, but not the degree of aneuploidy, was associated with radiotherapy failure.…”
Section: Discussionsupporting
confidence: 83%
“…These percentages are lower than reported previously by other groups (Wright et al, 1990;Moriyama et al, 1991;Coombs et al, 1991;Jenkins et al, 1990;Iles & Chard, 1991), but are consistent with another series from our group (Jacobsen et al, 1990). We have not been able to confirm a correlation between DNA non-diploidy and c-erbB-2 protein immunoreactivity as indicated in our previous report on a more heterogeneous series (Berner et al, 1992).…”
Section: Dna Ploidy and S-phase Fraction In Bladder Can£cer 575supporting
confidence: 91%
“…In muscle-invasive bladder cancer the significance of DNA ploidy is less obvious (Lipponen et al, 1991;Jenkins et al, 1990;Jacobsen et al, 1989;Badalament et al, 1990;Wijkstrom et al, 1992;Hug et al, 1992). Even less is known about the clinical significance of the S-phase fraction (SPF) in muscle-invasive bladder cancer as determined by DNA FCM, though some correlation has been suggested between this parameter and metastatic regional lymph node involvement (Lipponen 1991;Shaaban et al, 1990) or survival (Lipponen et al, 1991;Jacobsen et al, 1992).…”
mentioning
confidence: 99%
“…Complete tumour re sponse to irradiation has been reported in 40-60% of the patients but no reliable method exists to predict the radia tion response [1,2,5,6].…”
Section: Introductionmentioning
confidence: 99%